Polygenic transmission and complex neuro developmental network for attention deficit hyperactivity disorder: Genome‐wide association study of both common and rare variants. Issue 5 (31st May 2013) - Yang, Li; Neale, Benjamin M.; Liu, Lu; Lee, S. Hong; Wray, Naomi R.; Ji, Ning; Li, Haimei; Qian, Qiujin; Wang, Dongliang; Li, Jun; Faraone, Stephen V.; Wang, Yufeng; et al.
Abstract Attention‐deficit hyperactivity disorder (ADHD) is a complex polygenic disorder. This study aimed to discover common and rare DNA variants associated with ADHD in a large homogeneous Han Chinese ADHD case–control sample. The sample comprised 1, 040 cases and 963 controls. All cases met DSM‐IV ADHD diagnostic criteria. We used the Affymetrix6.0 array to assay both single nucleotide polymorphisms (SNPs) and copy number variants (CNVs). Genome‐wide association analyses were performed using PLINK. SNP‐heritability and SNP‐genetic correlations with ADHD in Caucasians were estimated with genome‐wide complex trait analysis (GCTA). Pathway analyses were performed using the Interval enRICHment Test (INRICH), the Disease Association Protein–Protein Link Evaluator (DAPPLE), and the Genomic Regions Enrichment of Annotations Tool (GREAT). We did not find genome‐wide significance for single SNPs but did find an increased burden of large, rare CNVs in the ADHD sample (P = 0.038). SNP‐heritability was estimated to be 0.42 (standard error, 0.13, P = 0.0017) and the SNP‐genetic correlation with European Ancestry ADHD samples was 0.39 (SE 0.15, P = 0.0072). The INRICH, DAPPLE, and GREAT analyses implicated several gene ontology cellular components, including neuron projections and synaptic components, which are consistent with a neurodevelopmental pathophysiology for ADHD. This study suggested the genetic architecture of ADHD comprises both common and rare variants. Some common causal variants are likely to be shared between Han Chinese and Caucasians. Complex neurodevelopmental networks may underlie ADHD's etiology. © 2013 Wiley Periodicals, Inc.